KONSUMSI SUPLEMEN, ASUPAN ENERGI DAN KEBUGARAN JASMANI ATLET DI PERSTUAN BULUTANGKIS KABUPATEN KUDUS - Tri Hastin Khusmalinda; Siti Zulaekah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
Low consumption of supplements and energy intake can a decrease athlete performance because it is unable to restore stamina. The purpose of this study to determine whether there is a relationship between the consumption of supplements and energy intake of physical fitness athletes in Badminton Association of Kudus Regency. The type of this research is observational research with cross sectional approach. The sample size used was 33 athletes 18 years old. Sampling was done by using simple random sampling method. Taking supplement consumption data was obtained by filling out the questionnaire. Energy intake data were obtained through questionnaire food frequency questionnaire (FFQ) semi-quantitative. Physical fitness is obtained by performing a fitness test (beep test). Analysis relationship of the supplement consumption, energy intake and physical fitness using pearson product moment test. Respondents with consumption levels of supplements were often 84.8%, rarely 12.1% and never 3%. The results of energy intake study with severe deficit category 9.1%, moderate deficit absent or 0%, light deficit 3%, normal 45,5%, above requirement 42,4%.Physical fitness levels of athletes in the category of superior 21.2%, excellent 30.3%, above average 24.2%, an average of 15.2% and below the average of 9.1%. The result of analysis of the relationship between consumption of supplement with physical fitness showed p value = 0,477 and result of analysis of energy intake relationship with physical fitness showed p value = 0,535. The conclusion of this study is that there is no relationship between supplement consumption and energy intake on physical fitness.